Transfomasi Genetik : Peluang dan Tantangan - Retno Dwi Andayani; Widyana Rahmatika; Nur Fitriyah (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2023)
Plants have an important role in the development of human civilization. Human civilization progresses along with the development of the agricultural system and vice versa. Therefore humans have been trying to improve cultivated plants for thousands of years by trial and error. Traditionally, mankind have improved plants through repeated selection. However, the human population is increasing so rapidly that it necessitates a doubling of the increase in world food production. The program is constrained by the fact that we cannot increase arable land. So one solution is through biotechnology which is expected to produce more food without demanding an increase in agricultural land. At present, the application of biotechnology in agriculture can be done by genetic engineering such as genetic transformation and gene editing which are almost entirely aimed at forming transgenic plants. One of the developments in biotechnology that has been widely used is GMO (Genetically Modified Organism) or plants that have been genetically modified or are popularly known as transgenic plants. Genetic modification of plants has become the most promising approach for increasing crop yields, providing nutrients, exploiting stressed land, overcoming the energy crisis, and for producing cost-effective biopharmaceuticals.